Stabilization of fixed speed wind generator by using variable speed PM wind generator in multi-machine power system - Rosyadi, M.; Muyeen, S.M.; Takahashi, R.; Tamura, J. (2012)
This paper present stabilization control of fixed speed wind generator by using variable speed permanent magnet wind generator in a wind farm connected with multi-machine power system. A novel direct-current based d-q vector control technique of back to back converter integrated with Fuzzy Logic Controller for optimal control configuration is proposed, in which both active and reactive powers delivered to a power grid system are controlled effectively. Simulation analyses have been performed using PSCAD/EMTDC. Simulation results show that the proposed control scheme is very effective to enhance the voltage stability of the wind farm during fault condition.